2022
DOI: 10.1186/s13011-022-00502-1
|View full text |Cite
|
Sign up to set email alerts
|

School-based harm reduction with adolescents: a pilot study

Abstract: A pilot study of Safety First: Real Drug Education for Teens showed significant results pre to post curriculum with high school freshmen. Negative outcomes of drug education are linked to a failure to engage students because of developmentally inappropriate materials that include activities that have no relevance to real experiences of young people. The few harm reduction studies showed increased student drug related knowledge. Students were less likely to consume substances, and less likely to consume to harm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In a randomized controlled trial of a harm reduction cannabis education program in Australian high schools, Lester et al [ 21 ] found that students in the experimental group reported significantly less cannabis-related harms and significantly smaller increases in cannabis consumption rates at three years post-test. Fischer [ 22 ] conducted a pilot study of an American school-based harm reduction program, reporting that participating high school students exhibited a significant increase in harm reduction knowledge and behaviours from pre-test to post-test.…”
Section: Introductionmentioning
confidence: 99%
“…In a randomized controlled trial of a harm reduction cannabis education program in Australian high schools, Lester et al [ 21 ] found that students in the experimental group reported significantly less cannabis-related harms and significantly smaller increases in cannabis consumption rates at three years post-test. Fischer [ 22 ] conducted a pilot study of an American school-based harm reduction program, reporting that participating high school students exhibited a significant increase in harm reduction knowledge and behaviours from pre-test to post-test.…”
Section: Introductionmentioning
confidence: 99%